Clinical application value of metagenomic second-generation sequencing technology in hematologic diseases with and without transplantation - Zhang, Xia; Wang, Fang; Yu, Jifeng; Jiang, Zhongxing (Frontiers in Cellular and Infection Microbiology, 2023)
Hematological patients are at risk of infections due to immune reconstruction, immunosuppressants, and other factors. A retrospective study was conducted to evaluate the clinical impact of metagenomic next-generation sequencing (mNGS) in hematological patients with and without HSCT. Viruses were prevalent pathogens in both non-HSCT (44%) and HSCT (45%) patients, chiefly human cytomegalovirus and Epstein–Barr virus. In non-HSCT patients, Gram-negative bacilli accounted for 33% (predominantly Klebsiella pneumonia), and Gram-positive cocci accounted for 7% (predominantly Enterococcus faecium) of pathogens. However, Gram-negative bacilli accounted for 13% (predominantly Stenotrophomonas maltophilia), and Gram-positive cocci accounted for 24% (predominantly Streptococcus pneumonia) of pathogens in HSCT patients. Mucor was the most common fungus both in the non-HSCT and HSCT patient groups. The positive rate of pathogens detected by mNGS was 85.82%, which was higher than conventional detection (20.47%, P < 0.05). Patients with mixed infection accounted for 67.00%, among which the mixed infection of bacteria and virus (25.99%) was the most common. For the samples of pulmonary infection, 78 cases had pulmonary infection, the positive rate of traditional laboratory tests was 42.31% (33/78), and the positive rate of mNGS in peripheral blood was 73.08% (57/78), showing a statistical difference (P = 0.000). The non-HSCT patients had a higher frequency of Klebsiella pneumonia (OR=0.777, 95% CI, 0.697-0.866, P = 0.01) and Torque teno virus (OR=0.883, 95% CI, 0.820-0.950, P = 0.031) infections than HSCT patients, while the rates of Streptococcus pneumonia (OR=12.828, 95% CI, 1.378-119.367, P = 0.016), Candida pseudosmooth (OR=1.100, 95% CI, 0.987-1.225, P = 0.016), human betaherpesvirus 6B (OR=6.345, 95% CI, 1.105-36.437, P = 0.039) and human polyomavirus 1 (OR=1.100, 95% CI, 0.987-1.225, P = 0.016) infections were lower in non-HSCT patients. There were 25 pathogens, such as Leishmania, that could be detected by mNGS only. Therefore, mNGS of peripheral blood can be used as a substitute test method for hematological patients with pulmonary infection, the detection rate of mixed infections by mNGS was high, and mNGS has high clinical recognition rate and sensitivity in pathogen detection, and provides a basis for guiding the anti-infective treatment in hematological diseases with symptoms such as fever.